PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT INDO SUHAR JAYA, CILEUNGSI, BOGOR - Ahmad Mirza; Ratna Sari (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of motivation, work environment on the performance of employees of Indo Suhar Jaya Company. This research method is quantitative with a descriptive approach. Data collection methods used are primary data, and secondary data. Sampling techniques in this study used saturated sampling techniques much as 40 respondents. Data analysis using SPSS version 25. Data analysis techniques used are validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination test, hypothesis test. Partial testing for motivation variable (X1) obtained ttest > ttable (3.592 > 2.024), with a significance value (0.001 < 0.5), which means that motivation (X1) has a significant effect on employee performance (Y). Partial testing of hypotheses work environment (X2) obtained ttest > ttable (6.537 > 2.024), a significant value (0.000 < 0.5), which means that the work environment has a significant effect on employee performance (Y). Simultaneously hypothesis testing for the Ftest > Ftable (20.843 > 3.245), the value of significance (0.000 < 0.5). These mean that motivation (X1), work environment (X2) are simultaneously have a significant effect on employee performance (Y). Determination obtained by R Square of 0.530 means that the motivation variable (X1), work environment (X2) have an influence contribution of 53.0% on employee performance (Y). While the remaining 47.0% were influenced by other factors which is not studied on this research.